Analisis Permasalahan Seni Tani Dalam Menerapkan Konsep Community Supported Agriculture (CSA) - Alafgani, Fahmi Zamaludin; Setiawan, Iwan; Kadapi, Muhamad (Universitas Galuh, 2024)
In response to various problems related to the global food system, various Alternative Food Networks (AFN) have been developed over the last two decades. One of the AFN that has been widely implemented in the world is Community Supported Agriculture (CSA). The CSA approach offers an alternative community-based agricultural model based on the principles of locality and solidarity economy, where production, distribution and consumption practices are made distinct from the global food system. The growth of CSA has become increasingly widespread, starting from European countries, America, Australia to Indonesia. In reflecting on the growth and development of CSA in various countries, this study aims to analyze the problems and potential for the development of CSA in Tani Arts, considering that Seni Tani is one of two existing CSAs in Indonesia. This research was designed qualitatively using the case study method. Data collection techniques were carried out by non-participant observation, in-depth interviews and documentation. Existing data were then analyzed by analysis of literature studies, analysis of fishbone diagrams. The analysis of the literature study shows that CSA Seni Tani in general has implemented the main principles of the CSA concept, although it is not perfect because there are still contradictions in values that occur. The Fishbone Diagram analysis shows that there are four main problems in the application of CSA Seni Tani, namely first, product risk that does not match consumer expectations. Second, socialization regarding the concept of CSA is not optimal. Third, CSA in Seni Tani experienced fluctuations in active members. The four CSA Seni Tani have not yet reached many farmers in East Bandung as targets for collaboration partners.